Increasing Confidence Among Fourth Year Medical School Students Preparing For Residency Interviews - Shil Punatar; Alessandra Carrillo; Holly Proffitt (Mashhad University of Medical Sciences, 2023)
Background: The rise of COVID-19 has made changes in medical education and residency preparedness as residency interviews have shifted from an in person to virtual platform. This study looks at the differences between confidence scores based on the number of preparation events attended by the students in order to assess fourth year student confidence.Method: Survey research was conducted for this study using a non-experimental research design with an invited sample size of 125 medical students in their fourth year. The independent variable was the number of training sessions attended. The dependent variable was the confidence score of the student. Our team gathered data on the confidence of fourth year medical students as they prepared for virtual interviews and determined the differences, if any, in confidence in their ability to interview based on the amount of preparation.Results: The overall response rate was 28 percent out of a total of 124 possible participants. A total of 30 participants were used in analysis. Using linear regression, results demonstrate a statistically significant (p<.05) result and a strong moderate correlation (r=.549) of how many interview assignments and activities the students completed correlated positively with the overall confidence the student had in their interview performance. Conclusion: The findings of this study show a strong correlation between the level of participation in virtual interview preparedness events and the level of confidence in students preparing for interviews, demonstrating the importance of residency interview preparedness for virtual platforms.